2019
DOI: 10.3762/bjnano.10.222
|View full text |Cite
|
Sign up to set email alerts
|

Design of a nanostructured mucoadhesive system containing curcumin for buccal application: from physicochemical to biological aspects

Abstract: Mucoadhesive nanostructured systems comprising poloxamer 407 and Carbopol 974P® have already demonstrated good mucoadhesion, as well as improved mechanical and rheological properties. Curcumin displays excellent biological activity, mainly in oral squamous cancer; however, its physicochemical characteristics hinder its application. Therefore, the aim of this study was to develop nanostructured formulations containing curcumin for oral cancer therapy. The photophysical interactions between curcumin and the form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 96 publications
(179 reference statements)
0
6
0
Order By: Relevance
“…[ 45,46 ] An ideal mucoadhesive formulation should have (a) intense contact with the oral mucosa to enhance the bioavailability of drugs in the target tissue and (b) extended residence time at the site treatment to reduce the drug dosing. [ 38,47,48 ] The secretion of saliva by the salivary glands provides a thin coating of mucus on the mucosal surfaces. The major component of mucus is mucin.…”
Section: Theories Of Mucoadhesionmentioning
confidence: 99%
“…[ 45,46 ] An ideal mucoadhesive formulation should have (a) intense contact with the oral mucosa to enhance the bioavailability of drugs in the target tissue and (b) extended residence time at the site treatment to reduce the drug dosing. [ 38,47,48 ] The secretion of saliva by the salivary glands provides a thin coating of mucus on the mucosal surfaces. The major component of mucus is mucin.…”
Section: Theories Of Mucoadhesionmentioning
confidence: 99%
“…A texture analysis of the chitosan gels was prepared according Ferreira et al [28] with some modifications. A texture analyzer TA.XTplus (Stable Micro Systems, Godalming, UK) was used.…”
Section: Texture Analysis Of Chitosan Gelsmentioning
confidence: 99%
“…Therefore, a safer and more effective treatment is urgently needed to improve prognosis and reduce adverse reactions and complications post-treatment. Studies have shown that the preparation of curcumin made of the poloxamer-based thermosensitive gel has a great therapeutic effect on OSCC [ 17 ]. Curcumin also demonstrates excellent biological activity, which also has great advantages for OSCC.…”
Section: Subjectsmentioning
confidence: 99%
“…Thermosensitive gels have been studied as a scaffold for encapsulating dental pulp stem cells for cell delivery in tissue engineering, buccal applications for oral cancer therapy, intratumoral injection for anti-tumor therapy, etc. [ 16 , 17 , 18 ]. There have been several studies on its application in the oral cavity but no comprehensive summary.…”
Section: Introductionmentioning
confidence: 99%